The impact of human resources flexibility in re-engineering banking operations (Field study in the public commercial banks in Lattakia Governorate) - صالح حلا; رامي محمد; علي البهلول (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study mainly aimed at determining the impact of human resources flexibility in its dimensions (skill flexibility, behavior flexibility) in re-engineering banking operations in commercial banks in Lattakia Governorate. The researcher followed the analytical descriptive approach in her study, and a set of methods, including reliance on secondary and primary data, through a questionnaire designed and distributed to (140) respondents, from which (133) were retrieved, and (127) questionnaires were valid for analysis, and the research community consisted of a cadre Employees in the departments of public commercial banks operating in the province of Lattakia, then the SPSS program version /21/ was relied upon as a tool for analyzing the available data. The study concluded that the employees of the bank do not work to develop their skills continuously, and the employees of the bank do not possess multiple skills that are used in different jobs, and that there is a statistically significant effect of the flexibility of human resources in re-engineering banking operations in the public commercial banks in Lattakia, and the total average reached answers The sample members for the skill flexibility variable are 2.9678, and this indicates a lack of skill flexibility among workers in public commercial banks operating in Lattakia Governorate. The study recommended: The need for bank employees to continuously develop their skills, and the need for bank employees to possess multiple skills that are used in different jobs, and the need to pay attention to skill flexibility as one of the dimensions of human resources flexibility through that employees work to continuously develop their skills, and to have Multiple skills that are used in different jobs, and that they can accomplish a wide range of tasks available due to their role in influencing the re-engineering of banking operations in the public commercial banks in Lattakia..